2020
DOI: 10.4081/jae.2020.1057
|View full text |Cite
|
Sign up to set email alerts
|

Improving olive mechanical harvesting using appropriate natural frequency

Abstract: The good performance of olive mechanical harvesting by shaking depends on the suitable values of limb vibrator operating parameters (frequency and amplitude). Mathematical models of a single degree of freedom (S.D.F.M) and two degrees of freedom (T.D.F.M) were used to estimate the natural frequency (FN) of olive fruit stem system. The results from these models indicated that the FN values were 33.9, 31.9, and 28.0 Hz for the full mature stage, half-ripe olive, and full-ripe olive respectively. Branch vibrator … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Increasing PTO shaft speed, vibration amplitude and vertical height clamp position decreased operational cost that is may be due to the increase in machine productivity under the all-mentioned parameters. This is in agreement with Alzoheiry, et al (2020) who stated that the good performance of olive mechanical harvesting by shaking depends on the suitable values of vibrator operating parameters (frequency and amplitude). CONCLUSION The main objective of the present investigation was to manufacture and evaluate the performance of a local tractormounted machine from local material to be used for harvesting olive.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Increasing PTO shaft speed, vibration amplitude and vertical height clamp position decreased operational cost that is may be due to the increase in machine productivity under the all-mentioned parameters. This is in agreement with Alzoheiry, et al (2020) who stated that the good performance of olive mechanical harvesting by shaking depends on the suitable values of vibrator operating parameters (frequency and amplitude). CONCLUSION The main objective of the present investigation was to manufacture and evaluate the performance of a local tractormounted machine from local material to be used for harvesting olive.…”
supporting
confidence: 92%
“…The results from these models indicated that the FN values were 33.9, 31.9, and 28.0 Hz for the fully mature stage, half-ripe olive, and full-ripe olive respectively. Branch vibrator was operated at three levels of frequency and 3 levels of amplitude at a vibration time of 10 s ( Alzoheiry, et al, 2020). However, to understand the effects of mechanical harvesting on olive productivity, further research is required.…”
Section: Introductionmentioning
confidence: 99%
“…According to recent research, fruit trees that are shaken may experience very large damping losses, depending on how far up the shaker is linked to the tree trunk (Horvath and Sitkei, 2001;Alzoheiry et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Manzanilla was inferior to those picked manually. Alzoheiry et al (2020) estimated the natural frequency (FN) of olive fruit stem system using one and two degrees of freedom models. Their result indicated that the FN value of full mature stage was 33.9 Hz, half-ripe olive was 31.9 Hz, and 28.0 Hz for full-ripe olive.…”
Section: Introductionmentioning
confidence: 99%